Floristic findings of rare species in the Bila River valley (Lugans’ka oblast’) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Data about finding of 24 rare species in Donets’k chain of hills are given (Ephedra distachya L., Cystopteris fragilis (L.) Bernh., Asplenium septentrionale (L.) Hoffm., A. trichomanes L., Aconitum rogoviczii Wissjul., Adonis wolgensis Steven, Anemone ranunculoides L., Pulsatilla pratensis (L.) Mill., Corydalis paczoskii N.Busch, C. solida (L.) Clairv., C. marschalliana (Pall. ex Willd.) Pers, Cerastium pseudobulgaricum Klokov, Mercurialis perennis L., Allium lineare L., Gagea bohemica (Zauschn.) Schult. et Schult. f., Fritillaria ruthenica Wikstr., Tulipa ophiophylla Klokov & Zoz, T. quercetorum Klokov & Zoz, Hyacinthella pallasiana (Steven) Losinsk, Ornithogalum boucheanum (Kunth) Asch., Scilla siberica Haw., Crocus reticulatus Steven ex Adams, Iris pumila L., Stipa capillata L.). The age structure of the coenopopulations of Fritillaria ruthenica and the Hyacinthella pallasiana is elucidated. Additional nature areas in Bila River valley are recognized for establishing new protected territories.
Keywords: new floristic records, condition of population, rare species, Donets’k chain of hills.